Imperio desde los márgenes: Un estudio de la obra de fray Pedro González de Agüeros y sus planes reformistas de las fronteras del sur de la América meridional a finales del siglo XVIII - Rex Galindo, David (Anuario de Historia de América Latina, 2020)
This article analyzes missionary Fray Pedro González de Agüeros’s writings on frontier missions in the Chiloé archipelago in southern Chile held by the Franciscan College of Propaganda Fide in Ocopa at the end of the 18th century. González de Agüeros supported the application of the Bourbon reforms on his college’s frontier missions. Through his writings, I explore the nature of the relationship between the monarchy, the state and the frontier territories in Spanish America in the late colonial period. I further examine his adherence to a reformist agenda that defended the militarization, socioeconomic progress, population settlement, and public education in the frontiers of empire as a means to improve the local situation and royal control as well as to continue Spanish expansion along the Pacific coast and islands. Focusing mainly on the province of Chiloé, south of the kingdom of Chile, and the territories to the South, the missionary’s work demonstrates an adaptation between the religious discourse and the new administrative and political realities that characterize the relationship between the frontiers of Spanish America, the Hispanic monarchy and the state during the final period of Bourbon reforms. In this sense, I intend to demonstrate that González de Agüeros’s ideas echoed contemporary discourses of political and economic reform in Spanish America typical of the Bourbon reforms.